2012
DOI: 10.1371/journal.pone.0040903
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Epileptiform EEG Activity in Children during Mask Induction of Anaesthesia with Brief Administration of 8% Sevoflurane

Abstract: BackgroundA high incidence of epileptiform activity in the electroencephalogram (EEG) was reported in children undergoing mask induction of anaesthesia with administration of high doses of sevoflurane for 5 minutes and longer. This study was performed to investigate whether reducing the time of exposure to a high inhaled sevoflurane concentration would affect the incidence of epileptiform EEG activity. It was hypothesized that no epileptiform activity would occur, when the inhaled sevoflurane concentration wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In our study, induction of VIGA with sevoflurane resulted in the presence of EPs in patients' EEGs at a similar rate to previous studies concerning the presence of EPs during GA with sevoflurane [1][2][3][5][6][7]26,27]. We observed significantly higher HR values in patients induced with the VCRII technique when the EPs appeared; therefore, their appearance resulted in haemodynamic instability, since patients who were induced with the VCRII technique but did not show EPs showed lower haemodynamic parameters at the same stages (Table 3).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, induction of VIGA with sevoflurane resulted in the presence of EPs in patients' EEGs at a similar rate to previous studies concerning the presence of EPs during GA with sevoflurane [1][2][3][5][6][7]26,27]. We observed significantly higher HR values in patients induced with the VCRII technique when the EPs appeared; therefore, their appearance resulted in haemodynamic instability, since patients who were induced with the VCRII technique but did not show EPs showed lower haemodynamic parameters at the same stages (Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…Both volatile induction of general anaesthesia (VIGA) with sevoflurane and intravenous induction of general anaesthesia with propofol may induce seizure-like movements or seizures accompanied by haemodynamic instability [1,2], which are defined as clinically manifest events with confirmatory electroencephalographic patterns. Seizures during VIGA with sevoflurane were observed with an incidence of 5% in children [2], whereas subclinical activity in children's electroencephalographic recordings (without clinically manifest events) during VIGA with sevoflurane have been reported to appear in 20% of cases [1,3], as compared to 47% in adults breathing spontaneously [4]. The appearance of these findings during VIGA with sevoflurane in children is known to increase to 88% with controlled hyperventilation and even up to 100% with hypocapnia [2].…”
Section: Introductionmentioning
confidence: 99%
“…In another study from the own department on EEG effects during induction of anaesthesia with sevoflurane in children, also no gender effect was found [13].…”
Section: Discussionmentioning
confidence: 88%
“…[1] Some studies had shown that lower sevoflurane concentration during induction and shorter induction time can reduce the occurrence of epileptic discharge. [4,14] Iijima et al reported that nitrous oxide may diminish epileptogenic effects of sevoflurane in patients with epilepsy. [5] And the addition of alfentanil in the induction process of sevoflurane may have a protective effect on sevoflurane induced epileptic discharges.…”
Section: Discussionmentioning
confidence: 99%